The specificity of the national identity in the epoch of globalization - Liahchylin, Anatol; Astrouskaya, Tatsiana (Creativity Studies, 2008)
This article is devoted to the analysis of the national identity in the epoch of globalization. With the impact of globalization things and relations have changed rapidly. The authors try to show that the same situation happened to the national identity, the borders of which are becoming more and more flexible and movable. This situation can be used for the purpose of the renaissance of the national identity. However, it is possible only in the way of the combination of support from the state with realization by every nation of its own specificity and singularity. Tautinės tapatybės savitumas globalizacijos epochoje Santrauka. Analizuojama tautinė tapatybė globalizacijos sąlygomis. Globalizacijos procesas savaime sukelia didžiulių valstybės ir tautinio tapatumo pokyčių, tad tapatumo ribos tampa vis lankstesnės. Straipsnio autorių manymu, tokia situacija gali inspiruoti tautinio tapatumo renesansą. Tačiau tai įmanoma tik puoselėjant nacionalinės valstybės unikalumą ir savitumą. Reikšminiai žodžiai: siena, globalizacija, tautinė tapatybė, tautinė valstybė, Baltarusijos Respublika. First Published Online: 14 Oct 2010